When the Carousel stops turning … What shall we say about the slide show? - Langford, Martha (Intermédialités / Intermediality, 2014)
When we speak of the slide show, we are speaking of many things. Photographic art, social documentary photography, information, entertainment, education, discipline, and punishment… the Carousel projector (1961–2004) was part of all these histories, and to an appreciable degree these cultural products shared not just a technical apparatus, but its language and embodied effects. As these machines disappear, we are increasingly reliant on visual and textual documents, as well as creative translations, to try to understand these works, their meaning and effects. My paper interrogates these accounts to grasp what was particular to the slide show medium, regardless of authorial intent, subject matter, and the increasingly porous division between high and low cultures.